Proximate and Micronutrient Composition of Pandanus species in Andaman and Nicobar Islands, India - Jaisankar, I.; Varadan, R. Jayakumara; Blesy, G.M.; Asokan, Hari Nivas; Moses, Manasseh Ezekiel; Prabu, S. Lakshmana (Indian Forester, 2024)
Better nutrition is essential for a healthy living of which fruits play a major role. Andaman and Nicobar Islands, an excellent hub for Pandanus species belonging to Pandanaceae family speaks out its importance that the plant parts have been effectively used by its tribals in their livelihood due to its excellent nutritional properties to be used in beaucoup fields for a healthy living. Therefore, proximate composition and micronutrient analysis in the fruits and seeds of three selected species namely Pandanus lerum, P. tectorius and P. odorifer collected from different locations of Andaman and Nicobar Islands were studied using standard procedures where P. lerum had good levels of carbohydrate (84.59g/100g) in pulp and fat (62.39g/100g) in seed whereas P. odorifer pulp had significant levels of crude fibre (21.77g/100g) and P. tectorius seed possessed a higher protein (19.45g/100g) content. Better concentration of micronutrients was also observed in which P. lerum seed had higher levels of Mn (17.70 ppm), Mg (1102.33 ppm) and K (398.83 ppm) respectively. On the contrary, P. odorifer and P. tectorius pulp possessed higher levels of Fe (95.66 ppm) and Zn (15.81 ppm) respectively suggesting Pandanus fruit has sound pharmaceutical and nutraceutical application.